Is beta-carotene consumption associated with thyroid hormone levels? - Farasati Far, Bahareh; Broomand Lomer, Nima; Gharedaghi, Hossein; Sahrai, Hadi; Mahmoudvand, Golnaz; Karimi Rouzbahani, Arian (Frontiers in Endocrinology, 2023)
The thyroid hormones play a pivotal role in various physiological processes, including growth, metabolism regulation, and reproduction. While non-modifiable factors are known to impact thyroid function, such as genetics and age, nutritional factors are also important. Diets rich in selenium and iodine are conventionally acknowledged to be beneficial for the production and release of thyroid hormones. Recent studies have suggested a potential link between beta-carotene, a precursor to vitamin A (retinol), and thyroid function. Beta-carotene is known for its antioxidant properties and has been shown to play a role in the prevention of various clinical conditions such as cancer and cardiovascular and neurological diseases. However, its impact on thyroid function is still unclear. Some studies have suggested a positive association between beta-carotene levels and thyroid function, while others have found no significant effect. Conversely, the hormone produced by the thyroid gland, thyroxine, enhances the conversion of beta-carotene to retinol. Furthermore, vitamin A derivatives are being explored as potential therapeutic options for thyroid malignancies. In this review, we highlight the mechanisms through which beta-carotene/retinol and thyroid hormones interact and review the findings of clinical studies examining the association between beta-carotene consumption and thyroid hormone levels. Our review underscores the need for further research to clarify the relationship between beta-carotene and thyroid function.